Characteristics of Cellular Lightweight Concrete Bricks Using Rice Husk Ash and Nickel Slag Waste - Ahmad, Irma Aswani; Taufieq, Nur Anny Suryaningsih; Pertiwi, Nurlita (Indonesian Journal of Fundamental Sciences, 2025)
Abstract. The construction industry increasingly demands environmentally sustainable materials that reduce dependency on non-renewable resources. This study investigates the potential of rice husk ash (RHA) as a partial cement substitute and nickel slag as a fine aggregate replacement in the production of Cellular Lightweight Concrete (CLC) bricks. Both materials are industrial and agricultural wastes rich in silica, offering chemical and physical properties suitable for lightweight concrete applications. The research aims to evaluate the compressive strength of CLC bricks by incorporating RHA and nickel slag, with a particular focus on the influence of sand fineness. Three levels of sand gradation were tested, corresponding to Zone 2 (coarser), Zone 3, and Zone 4 (finest) based on sieve analysis. Specimens were cast and tested under standard conditions to assess their mechanical performance. The results indicate that sand fineness significantly affects the compressive strength of the bricks. Zone 2 sand produced the highest compressive strength (0.21 MPa), followed by Zone 4 (0.15 MPa) and Zone 3 (0.08 MPa). The decline in strength with finer sand is attributed to increased porosity and reduced interparticle friction, which disrupts bonding within the matrix. Furthermore, characterization results confirm that nickel slag fulfills the physical requirements of fine aggregates. This study demonstrates that combining RHA and nickel slag in CLC bricks is feasible and can support the development of more sustainable, non-structural construction materials with optimized mechanical performance. Keywords: CLC, rice husk ash, nickel slag, compressive strength, sand fineness